Truth Commissions and Public Inquiries: Addressing Historical Injustices in Established Democracies - Stanton, Kim Pamela
In recent decades, the truth commission has become a mechanism used by states to address historical injustices. However, truth commissions are rarely used in established democracies, where the commission of inquiry model is favoured. I argue that established democracies may be more amenable to addressing historical injustices that continue to divide their populations if they see the truth commission mechanism not as a unique mechanism particular to the transitional justice setting, but as a specialized form of a familiar mechanism, the commission of inquiry. In this framework, truth commissions are distinguished from other commissions of inquiry by their symbolic acknowledgement of historical injustices, and their explicit “social function” to educate the public about those injustices in order to prevent their recurrence. Given that Canada has established a Truth and Reconciliation Commission (TRC) on the Indian Residential Schools legacy, I consider the TRC’s mandate, structure and ability to fulfill its social function, particularly the daunting challenge of engaging the non-indigenous public in its work. I also provide a legal history of a landmark Canadian public inquiry, the Mackenzie Valley Pipeline Inquiry, run by Tom Berger. As his Inquiry demonstrated, with visionary leadership and an effective process, a public inquiry can be a pedagogical tool that promotes social accountability for historical injustices. Conceiving of the truth commission as a form of public inquiry provides a way to consider the transitional justice literature on truth commissions internationally along with the experiences of domestic commissions of inquiry to assemble strategies that may assist the current TRC in its journey. SJD